On-farm increased production, income and water-use efficiency through micro-irrigation in India - Taley, S. M., author; Patode, R. S., author; Mankar, A. N., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
On-farm production, income and water use efficiency for horticultural and other agronomical crops in terms of the benefit cost ratio micro-irrigation systems were calculated, and it is observed that B.C. ratio of drip irrigation was greater than conventional methods of irrigation. The water use efficiency was also higher than for conventional methods of irrigation. The monetary gains from micro-irrigation systems were larger than for conventional methods of irrigation for all crops. Information on water use efficiency, productivity and advantages of micro-irrigation compared to conventional irrigation methods is compiled and presented.
USCID/EWRI conference
Micro-irrigation in India
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.